Pengembangan Aplikasi Absensi Siswa Berbasis Web Pada SMKN 1 Karawang - Nur Mauluddin Pahrevi (Program Studi Teknik Informatika Universitas Nusa Putra, 2024)
The Student Attendance System application is a platform that provides information regarding student attendance records at school. At SMKN 1 Karawang, the process of recording student attendance has been carried out manually, starting from recording student attendance, managing attendance data, to preparing the final report. Manual approach This has proven to be less efficient and often produces inaccurate attendance data. Other problems that often arise related to document archiving include loss of notebooks or archives, difficulties in searching for data, and damage to archives. The aim of this research is to design a student attendance system that can makes it easier to manage student attendance data, especially by utilizing a web-based student attendance information system. This approach involves the use of Waterfall model development software and the PHP programming language with a MySQL database. The advantages and results of this web-based student attendance information system are that it provides a variety of features that will make it easier for teachers to manage student attendance data.